2019
DOI: 10.2478/fon-2019-0043
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between self-directed learning readiness, learning attitude, and self-efficacy of nursing undergraduates

Abstract: Objective The purposes of this study were to analyze the influencing factors of self-directed learning readiness (SDLR) of nursing undergraduates and explore the impacts of learning attitude and self-efficacy on nursing undergraduates. Methods A total of 500 nursing undergraduates were investigated in Tianjin, with the Chinese version of SDLR scale, learning attitude questionnaire of nursing college students, academic self-efficacy scale, and the general information questionnaire. Result The score of SDLR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…The results support the findings of all studies investigating the correlation between selfdirected learning and self-efficacy in learning, that a significant relationship exists between selfdirected learning and self-efficacy in learning [28,29]. Hence, to improve public senior high school students' self-directed learning, educators should foster their self-efficacy in learning.…”
Section: Relationship Between Self-directed Learning and Self-efficacy In Learningsupporting
confidence: 87%
See 3 more Smart Citations
“…The results support the findings of all studies investigating the correlation between selfdirected learning and self-efficacy in learning, that a significant relationship exists between selfdirected learning and self-efficacy in learning [28,29]. Hence, to improve public senior high school students' self-directed learning, educators should foster their self-efficacy in learning.…”
Section: Relationship Between Self-directed Learning and Self-efficacy In Learningsupporting
confidence: 87%
“…The demonstration of Self-Efficacy in Learning is cited as one of the manifestations of self-directed learning [3,4,27]. Studies investigating the correlation between self-directed learning and self-efficacy in learning generally affirm a significant relationship between self-directed learning and self-efficacy in learning [28,29].…”
Section: Self-directed Learning and Self-efficacy In Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…The results further suggest that students who boost their self-efficacy can increase their performance in solving problems through studying (Hayat et al, 2020;Zhou et al, 2020). In addition, prior studies found a strong positive association with the academic self-efficacy of students and their SDLR (Meng et al, 2019;Zhang et al, 2018). In general, previous research has shown that the http://www.ijlter.org/index.php/ijlter SDLR of students was strongly associated with their problem-solving performance, and the performance to solve problems could be facilitated by enhancing the SDLR of students (Choi et al, 2014;Struyf, 2005;Williams, 2004;Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 54%